Новый комплекс с пальчатыми фибулами с некрополя у с. Лучистого - Айбабин, А.И.; Хайрединова, Э.А. (Материалы по археологии, истории и этнографии Таврии, 1996)
A new complex, found in vault 77, Luchistoe village, in a western part of the cemetery near Demerdji mountain, is of great importance for dating brooches with concentric rhombs on the footpart and Aquileya-type brooches.